2020
DOI: 10.1186/s41687-020-00236-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the ability to participate in and satisfaction with social roles and activities in patients in outpatient rehabilitation

Abstract: Background: One of the main aims of rehabilitation is to improve participation. Patient-Reported Outcomes Measurement Information System (PROMIS®) item banks 'Ability to Participate in Social roles and Activities, (PROMIS-APS) and 'Satisfaction with Social Roles and Activities' (PROMIS-SPS) are promising options to measure participation, but the literature on PROMIS measures of (satisfaction with) participation across diagnoses in rehabilitation is limited. Therefore, the objective of this study was to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…We evaluated the ability to participate in social activities (PROMIS-APS) in patients with three rheumatic diseases and its association with other social variables and clinical factors. We found that, despite the epidemiological and clinical differences between the three diseases, abnormalities in patients’ ability to participate in social activities were very similar, and the mean scores of the PROMIS-APS in these three rheumatic diseases were much lower than those of the reference population and patients with other musculoskeletal conditions [ 29 ] Likewise, we did not observe differences in the PROMIS score for social activities in the different settings, except for mobility, which was less affected in patients with SLE. The greater impairment in mobility observed in patients with RA and SpA could be associated with older age and more frequent arthritis than in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the ability to participate in social activities (PROMIS-APS) in patients with three rheumatic diseases and its association with other social variables and clinical factors. We found that, despite the epidemiological and clinical differences between the three diseases, abnormalities in patients’ ability to participate in social activities were very similar, and the mean scores of the PROMIS-APS in these three rheumatic diseases were much lower than those of the reference population and patients with other musculoskeletal conditions [ 29 ] Likewise, we did not observe differences in the PROMIS score for social activities in the different settings, except for mobility, which was less affected in patients with SLE. The greater impairment in mobility observed in patients with RA and SpA could be associated with older age and more frequent arthritis than in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we found that improved PROMIS scores for social satisfaction, mobility, company, older age, and lower frequency of depression were independently associated with the ability to participate in social activities (PROMIS-APS). While these aspects have not been evaluated in this type of patient, other studies on patients with musculoskeletal and neuromuscular involvement revealed that participation, as assessed using the PROMIS questionnaire, is associated with better quality of life, greater social satisfaction, and less frequent depression [ 4 , 29 ]. As for age, we found that older patients were more able to participate in social activities.…”
Section: Discussionmentioning
confidence: 99%
“…A higher score indicates greater satisfaction with social roles and activities. Evidence for the validity and sensitivity to change of versions of the scale has been reported (Tamminga et al, 2020; Terwee et al, 2019). The scale was developed for individuals 18 or above in age.…”
Section: Methodsmentioning
confidence: 99%
“…Our social activity measures are drawn from the PROMIS (Patient Reported Outcomes Measurement Information System) measurement bank and have been evaluated across multiple populations. [17][18][19] AwD research study samples are frequently composed of persons who identify their race as White and who have a specific diagnosis such as spinal cord injury, multiple sclerosis, or polio, 20 which represent some of the common conditions found among persons AwD, but often do not include other conditions that cause disability. Guidelines from the United States federal funding agencies including the National Institutes of Health and the National Institute on Disability, Independent Living, and Rehabilitation Research 21 have required researchers to improve the racial and ethnic diversity of their study samples, given the substantial differences in health and wellness outcomes for non-White individuals in the United States.…”
Section: Introductionmentioning
confidence: 99%